Handheld real-time PCR device. Issue 3 (12th January 2016) - Ahrberg, Christian D.; Ilic, Bojan Robert; Manz, Andreas; Neužil, Pavel
Abstract : World's smallest, fully autonomous, handheld real-time PCR was shown in this contribution. The device can quickly process up to four samples at a time with detection capability of a single DNA copy. The fully integrated system includes all required electronics for fluorescence measurement, data viewing (LCD display) and processing, and is ideal for use in small clinics and point-of-care applications. Abstract : Here we report one of the smallest real-time polymerase chain reaction (PCR) systems to date with an approximate size of 100 mm × 60 mm × 33 mm. The system is an autonomous unit requiring an external 12 V power supply. Four simultaneous reactions are performed in the form of virtual reaction chambers (VRCs) where a ≈200 nL sample is covered with mineral oil and placed on a glass cover slip. Fast, 40 cycle amplification of an amplicon from the H7N9 gene was used to demonstrate the PCR performance. The standard curve slope was −3.02 ± 0.16 cycles at threshold per decade (mean ± standard deviation) corresponding to an amplification efficiency of 0.91 ± 0.05 per cycle (mean ± standard deviation). The PCR device was capable of detecting a single deoxyribonucleic acid (DNA) copy. These results further suggest that our handheld PCR device may have broad, technologically-relevant applications extending to rapid detection of infectious diseases in small clinics.